Chemical Constituents of Essential Oil of the Leaves of Eryngium foetidum from Bangladesh - Chowdhury, Jasim Uddin; Nandi, Nemi Chandra; Yusuf, Mohammed (Bangladesh Journal of Scientific and Industrial Research, 2008)
The essential oil of leaves of Eryngium foetidum from Bangladesh was analyzed by GC-MS. Sixty three compounds have been identified with (E)-2-dodecenal (37.4 %), dodecanoic acid (10.7 %), trans-2-dodecanoic acid (9.7 %), (E)-2-tridecenal, (6.7 %), duraldehyde (5.1 %) and tetradecanal (4.4 %) as the major constituents. Bangladesh J. Sci. Ind. Res. 42(3), 347-352, 2007